High school students' summer jobs and their ensuing labour market achievement - Iris J. Y. Wang; Kenneth Carling; Ola Nääs (Institute for Labour Market Policy Evaluation (IFAU), 2006)
This paper seeks to determine the effect of summer jobs offered by the public sector on high-school students' labour market achievement by use of quasi-experimental data. Many municipalities in Sweden offer summer jobs within their organizations to high-school students. The municipality of Falun randomly allocates about 200 such summer jobs per year by a lottery. Because of this, the effect of a summer job might be determined while the issue of self-selection bias is controlled. Our study finds that summer jobs slightly improve the earnings immediately after graduation from high school, but the effect does not persist.
Keywords: C41; C93; J68; 330; intention-to-treat; on-treatment; Wilcoxon-Mann-Whitney test; Schüler; Junge Arbeitskräfte; Urlaub; Bildungsertrag; Stichprobenverfahren; Schweden